Soil quality and its assessment: A review - KARTHIKEYAN, K.; KUMAR, NIRMAL; PRASAD, JAGDISH; SRIVASTAVA, RAJEEV (Journal of Soil and Water Conservation, 2021)
The competitive demand from different sectors and deteriorating resource base necessitated to deliberate soil quality and its functionality and way to improve it for higher productivity of produce without deteriorating the ecosystem and in this context, the historical perspective of soil quality and its indicators and methods of quality evaluation have been reviewed and presented here for the benefit of larger readership.